2019
DOI: 10.3389/fpls.2019.00942
|View full text |Cite
|
Sign up to set email alerts
|

A Physic Nut Stress-Responsive HD-Zip Transcription Factor, JcHDZ07, Confers Enhanced Sensitivity to Salinity Stress in Transgenic Arabidopsis

Abstract: Homeodomain-leucine zipper (HD-Zip) transcription factors are reported to play crucial roles in the growth, development, and stress responses of plants. However, there is little knowledge of the molecular mechanisms involved in physic nut’s stress tolerance generally, or the functions of its HD-Zip genes. In the present study, a HD-Zip family transcription factor, designated JcHDZ07 , was isolated from physic nut. Expression profile analysis showed that salinity st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…For proline content and CAT activity, the method in our previously reported paper was used to detect the activity of CAT and the content of proline (Tang et al, 2019a).…”
Section: Physiological Indices Analysismentioning
confidence: 99%
“…For proline content and CAT activity, the method in our previously reported paper was used to detect the activity of CAT and the content of proline (Tang et al, 2019a).…”
Section: Physiological Indices Analysismentioning
confidence: 99%
“…In contrast, transgenic plants had higher relative electrical leakage and malonaldehyde content than wild-type plants under salinity stress conditions but reduced survival rates, proline content, catalase, and superoxide dismutase activity [79]. Homeodomain-leucine zipper I (HD-Zip) is an essential family of TFs that play crucial roles in responding to various abiotic stressors.…”
Section: Hd-zipmentioning
confidence: 99%
“…Many reports indicate that HD-Zip I TFs from different plant species are involved in developmental adaptations to environmental stress (Mishra et al, 2012;Sen et al, 2017;Tang et al, 2019;Wu et al, 2016;Yang et al, 2018;Zhang et al, 2012). For example, AtHB7 was upregulated in response to salt treatment (Söderman et al, 1994), and the HD-Zip I γ-clade gene MtHB1 from Medicago truncatula was shown to be regulated by salt stress (Ariel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…ABA, drought, and salt induced the expression of CaHDZ12 in Chickpea, which positively affects various plant physiological and biochemical parameters, and CaHDZ12 overexpression (OE) plants were better adapted to adverse environments (Sen et al, 2017). Overexpression of HD-Zip I TF JcHDZ07, isolated from physic nut, enhanced sensitivity to salinity stress in transgenic Arabidopsis (Tang et al, 2019). The HD-Zip I TF SlHB2 was cloned from tomato and used to generate SlHB2 RNA interference (RNAi) transgenic plants.…”
Section: Introductionmentioning
confidence: 99%